Autonomous surveillance for biosecurity. Issue 4 (April 2015) - Jurdak, Raja; Elfes, Alberto; Kusy, Branislav; Tews, Ashley; Hu, Wen; Hernandez, Emili; Kottege, Navinda; Sikka, Pavan
Highlights Maps autonomous surveillance solutions to biosecurity problems. Explores three classes of biosecurity problem in vectors, plants, and water. Identifies current gaps that can be addressed by autonomous surveillance. Discusses application areas of opportunity for autonomous surveillance in biosecurity.